2020
DOI: 10.1002/adma.201908411
|View full text |Cite
|
Sign up to set email alerts
|

Shadow Epitaxy for In Situ Growth of Generic Semiconductor/Superconductor Hybrids

Abstract: The quality of interfaces and surfaces is crucial for the performance of nanoscale devices. A pertinent example is the close tie between current progress in gate-tunable and topological superconductivity using semiconductor/superconductor electronic devices and the hard proximity-induced superconducting gap obtained from epitaxial indium arsenide/aluminium heterostructures. Fabrication of devices requires selective etch processes; these only exist for InAs/Al hybrids, which precludes the use of other, potentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(138 citation statements)
references
References 50 publications
(265 reference statements)
8
130
0
Order By: Relevance
“…Finally, we demonstrate a new concept for merging the NC geometry with pre-defined substrate structures to enable in situ patterning of epitaxial superconductors, which have been shown to substantially enhance the performance of hybrid devices. [22][23][24]…”
Section: Doi: 101002/adma202100078mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we demonstrate a new concept for merging the NC geometry with pre-defined substrate structures to enable in situ patterning of epitaxial superconductors, which have been shown to substantially enhance the performance of hybrid devices. [22][23][24]…”
Section: Doi: 101002/adma202100078mentioning
confidence: 99%
“…[8] However the fragility of InSb is a challenge for devices based on InSb/Al epitaxial hybrids as all known etchings of Al also severely damages the InSb semiconductor and degrade device performance. Recently, in situ "shadow" approaches [18,[21][22][23][24] have been developed allowing patterning of epitaxial superconductor growth, yielding reproducible transport characteristics and observations of ballistic transport at B = 0 T for single NWs. These in situ shadow concepts, developed for single NWs, are however, incompatible with the NC geometry, where controlled shadows of the central junction region are required for most applications.…”
Section: In Situ Shadow Patterning Of Nanocrossesmentioning
confidence: 99%
“…Thus, for example, aluminium with a small superconducting gap and a small critical magnetic eld but large superconducting coherence length is a common choice. 1,13,16 For higher temperatures or higher magnetic elds operation, superconductors such as Nb and its alloys, 3,15,17,18 Pb, 19,20 or V, 21,22 are used. However, detailed analysis of these semiconductor/superconductor systems are just starting to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…A successful method to circumvent these problems is the in situ deposition of the superconducting material on the semiconductor nanowires. 18,[22][23][24] Another important issue is the residual material le on the structure from wet-chemical etching technique, that is normally used for the fabrication of Josephson junctions with a small gap. However, recently it was demonstrated that closely separated superconducting electrodes can also be achieved by shadow evaporation technique, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation